Psychological Semantic Parameters of Adolescents’ Conformism in the Measurement of Value Orientations - Popovych, Igor; BLYSKUN, Olena; HULIAS, Inesa; SHCHERBYNA, Vitalii; BATASHEVA, Nataliia; ALEKSIEIEVA, Mariia; CHALA, Tetiana (Lumen Publisching House, 2021)
The aim is to theoretically substantiate and empirically study the psychological semantic parameters of conformism of adolescence and to establish the relationship with values. Value orientations as an important regulatory mechanism of personality behaviorare revealed. Conformism is interpreted through social desirability as the individual’s desire for positive and constructive interaction, exchange with society, during which the individual obeys the latter, presenting himself in a favorable light. It is noted that young people often change their values under the pressure of “significant others” and society, presenting themselves in a favorable light, implementing conformal behavior. It is established that conformism correlates with value orientations (p<.01; p<.05). It is noted that respondents with a high level of conformism are characterized by a change in values under the influence of the environment and people with low levels –this trend is not observed. It has been studied that in adolescence there isa shift in the orientation of the individual from focusing on other people to focusing on their own meanings and values. It is determined that a person with a high level of conformism can neglect his own values, and therefore change his own behavior, which can be regarded as a “challenge to the environment”. It is offered to apply the received empirical results in training and to implement in educational and professional preparation of students-psychologists
Keywords: Conformity; values; student